Cover Feature: Hydrogen Bonding‐Based Layer‐by‐Layer Assembly of Nature‐Derived Eggshell Membrane Hydrolysates and Coffee Melanoidins in Single‐Cell Nanoencapsulation (ChemNanoMat 5/2022). Issue 5 (21st April 2022) - Han, Sang Yeong; Yun, Gyeongwon; Nguyen, Duc Tai; Kang, Eunhye K.; Lee, Hojae; Kim, Seulbi; Kim, Beom Jin; Park, Ji Hun; Choi, Insung S.
Abstract : Layer‐by‐layer (LbL) assembly of food waste‐derived materials, eggshell membrane hydrolysates and coffee melanoidins, is applied to the single‐cell nanoencapsulation (SCNE) of Saccharomyces cerevisiae . The hydrogen bonding‐based LbL process is extremely cytocompatible (viability > 99%), and the cell is protected from external assaults, such as heavy metals and UV‐B, after the SCNE. The shell's durability is further augmented by ferric ion‐mediated cross‐linking. More information can be found in the Research Article by Insung S. Choi et al. Photo credit: E. K. Kang.